Relationship Role of Peer Support Group with Quality of Life of ODHA - Priskila, Eva; Kurnia, Elitia (GLOBAL HEALTH SCIENCE GROUP, 2024)
The problem of HIV-AIDS is a common problem that must be addressed not only by ODHA but also by all the people connected with ODHA. The main problem experienced by ODHA is the decline in immune system that impact on the incidence of disease and decreased quality of life of ODHA. In addition to the physical, public acceptance of the existence of ODHA is also a factor related to the quality of life socially. The role of KDS is needed to improve the quality of life of ODHA. This study aims to determine the relationship of the Peer Support Group Role with the Quality of Life of ODHA in the Family Planning Association of Indonesia in Palangka Raya city. This research is a correlational research using cross sectional approach. The sample in this study amounted to 30 people determined by purposive sampling technique. Data collection using questionnaires with Likert Scale approach for WHOQOL-BREF and WHOQOL-BREF roles that have been standardized for quality of life. Data analysis using Spearman's Rank test statistic. The results of data analysis show that not all domains of 4 domains of quality of life have a significant relationship. Significant relation is found only in environmental domain with sig <α value is 0.03 <0.05 which means there is a significant relationship between the role of peer group and the quality of life of ODHA, in the environment domain. The conclusion of the study is that the role of KDS only relates to the quality of life of ODHA in the domain of the environment, not on the physical, psychological, and social relationships. Researchers suggest, the results of research used by PKBI to take policy in improving the quality of life of ODHA.